ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI STOCK UNDERPERFORMANCE IPOPADA PERUSAHAAN YANG LISTING DI BURSA EFEK INDONESIA TAHUN 1998-2012 - Robinson, Robinson; Pangestuti, Irene Rini Demi (Faculty of Economics and Business Diponegoro University, 2015)
This study aims to examine the factors that affect stock underperformance of IPOshares listed on the Indonesia Stock Exchange. This study uses eight independent variables, namely hot market (TIME), firm age (Age), underwriter reputation (UR), underpericing (UP), IPO volume (VOL), industry dummy (INDUM), capitalization of IPO (SIZE), with the dependent variable is the underperformance.The sampling technique used was purposive sampling criteria (1) The Company listed its shares on the Indonesia Stock Exchange, (2) Shares IPO companies experienced underperformance in the first period of one year, (3) the company has sufficient data to do research. The data sample obtained was 107 companies. The analytical method used is a multivariate regression. The assumption of classical test and hypothesis test using t- statistic, testing the coefficient of determination (R2), and the F-statistic to test the effect of model variables together with a significance level of 5%. This study also includes the classic assumption normality test, autocorrelation test, heteroscedasticity test, and multicollinearity test.Based on the data normality test results, the study shows that the data are normally distributed. Based on the test results with the classical assumption of multicollinearity test, autocorrelation and heteroscedasticity test did not find any data that deviate from the classical assumption. It shows that the data used in this study are qualified to use a multivariate regression model. From the analysis in this study showsage of the company during the IPO (Age) variable significant negative effect on stock underperformance. Underprice variable positive and significant effect on stock underperformance.Variable IPO volume (VOL), has a negative and significant impact on the stock underperformance. Variable hot market (TIME), industry dummy (INDUM), and capitalization IPO (SIZE) has a negative correlation coefficient and no significant effect on stock underperformance. Variable underwriter reputation (UR) has a positive correlation coefficient and no significant effect on stock underperformance.